Giant pH-responsive microgel colloidosomes: preparation, interaction dynamics and stability. Issue 5 (9th December 2015) - Morse, Andrew J.; Giakoumatos, Emma C.; Tan, Sin-Ying; Webber, Grant B.; Armes, Steven P.; Ata, Seher; Wanless, Erica J.
Abstract : Cross-linked PTBAEMA-stabilised colloidosomes are still present after the acid-induced latex-to-microgel transition unlike the analogous Pickering droplets which coalesce. Abstract : The interactions of two oil droplets grown in the presence of swollen, lightly cross-linked cationic poly( tert -butylamino)ethyl methacrylate (PTBAEMA) microgels was monitored using a high-speed video camera. Three oils ( n -dodecane, isopropyl myristate and sunflower oil) were investigated, each in the absence and presence of an oil-soluble cross-linker [tolylene 2, 4-diisocyanate-terminated poly(propylene glycol), PPG-TDI]. Adsorption of the swollen microgel particles was confirmed by interfacial tension, interfacial elasticity and dilational viscosity measurements on single pendant oil droplets, and assessment of the oscillatory dynamics for coalescing droplet pairs. Like the analogous bulk emulsions, particle adsorption alone did not prevent coalescence of pairs of giant Pickering emulsion droplets. However, prior addition of surface-active PPG-TDI cross-linker to the oil phase results in the formation of highly stable microgel colloidosomes via reaction with the secondary amine groups on the PTBAEMA chains. Colloidosome stability depended on the age of the oil–water interface. This reflects a balance between the adsorption kinetics of the PPG-TDI cross-linker and the microgel particles, each of which must be present at the interface to form a stable colloidosome. Colloidosome formation was virtually instantaneous in n -dodecane, but took up to 120 s in the case of isopropyl myristate. The impact of an acid-induced latex-to-microgel transition on the interaction of giant colloidosomes (originally prepared at pH 10 using isopropyl myristate) was also studied. This acid challenge did not result in coalescence, which is consistent with a closely-related study (A. J. Morse et al., Langmuir, 2014, 30 (42), 12509–12519). No evidence was observed for inter-colloidosome cross-linking, which was attributed to retention of an aqueous film between the adjacent pair of colloidosomes.